Low thermal expansion laminated alloy
By dispersing metal oxides within the structure of low thermal expansion alloys through controlled chemical composition and additive manufacturing processes, the alloy achieves both low thermal expansion and high 0.2% strength, addressing the limitations of existing alloys.
Patent Information
- Application Number
- JP2023166207
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-27
- Publication Date
- 2025-04-08
AI Technical Summary
Existing low thermal expansion alloys lack sufficient high 0.2% strength, which is essential for applications requiring both low thermal expansion and high mechanical strength.
The alloy achieves high 0.2% strength by dispersing metal oxides within its structure, specifically by adjusting the chemical composition to include appropriate amounts of C, Si, Mn, Ni, Co, and O, and ensuring proper oxygen incorporation during additive manufacturing to disperse metal oxides at an optimal area ratio of 0.50 to 2.00% in the austenitic structure.
This approach results in a low thermal expansion laminated alloy with a significantly enhanced 0.2% yield strength of 360 MPa or more, while maintaining a low average coefficient of thermal expansion of 1.00×10^-6 /°C or less between 18-28°C.
Smart Images

Figure 2025056621000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a low thermal expansion layered alloy. [Background technology]
[0002] Thermally stable Invar alloys are widely used as component materials for electronics and semiconductor-related equipment, laser processing machines, and ultra-precision processing equipment.
[0003] Meanwhile, additive manufacturing technology, or 3D printing technology, is attracting attention as it is said to be possible to manufacture products with complex shapes in a relatively short time.
[0004] Patent Document 1 relates to a low thermal expansion alloy having excellent low temperature stability, and discloses a low thermal expansion alloy containing, by mass%, C: 0.01% or less, Si: 0.05% or less, Mn: 0.05% or less, Ni: 34.5 to 36.0%, Co: 0.05 to less than 2.0%, Ni+0.8Co: 35.5 to 36.5%, with the balance being Fe and unavoidable impurities, having a solidification structure in which the dendrite secondary arm spacing is 5 μm or less, having an average thermal expansion coefficient at 100 to -190°C in the range of 0±0.1 ppm / °C, and an Ms point of -196°C or less.
[0005] Patent Document 2 relates to a heat treatment method for an additive manufacturing object, and discloses a heat treatment method for an additive manufacturing object, the heat treatment method comprising a step of holding an additive manufacturing object having a composition, in mass%, of 30.5-33.5% Ni, 4.0-6.5% Co, 0-0.60% Mn, 0-0.25% Si, 0-0.25% Cr, with the remainder being Fe and unavoidable impurities, at 900-1150°C. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Patent Publication No. 2022-35111 [Patent Document 2] JP 2022-47833 A Summary of the Invention [Problem to be solved by the invention]
[0007] An object of the present invention is to provide a low thermal expansion laminated alloy having high strength, specifically, high 0.2% proof stress. [Means for solving the problem]
[0008] The present inventors have conducted extensive research into methods for increasing the strength of low thermal expansion alloys, and have found that the strength can be increased by appropriately dispersing metal oxides within the structure.
[0009] The gist of the present invention is as follows.
[0010] The alloy contains, by mass%, C: 0-0.010%, Si: 0-0.050%, Mn: 0-0.050%, Ni: 30.00-37.00%, Co: 0-6.00%, O: 300-1000 ppm, and the balance is Fe and unavoidable impurities. The area ratio of metal oxides in austenite is 0.50-2.00%, and the average thermal expansion coefficient at 18-28°C is 1.00×10 -6 / °C or less. Effect of the Invention
[0011] According to the present invention, it is possible to provide a low thermal expansion laminated alloy having a high 0.2% proof stress. [Brief description of the drawings]
[0012] [Figure 1] FIG. 2 is a diagram showing the dispersion of metal oxides in the low thermal expansion laminated alloy of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] The low thermal expansion layered alloy of the present invention has a metal oxide dispersed in its structure to increase the strength of the low thermal expansion alloy. In order to disperse the metal oxide in its structure, it is necessary to introduce an appropriate amount of oxygen into the structure during additive manufacturing. The alloy powder that is the raw material for additive manufacturing also contains oxides, but the oxides are decomposed when heated during additive manufacturing. The low thermal expansion layered alloy of the present invention has an appropriate chemical composition that allows an appropriate amount of oxygen to be introduced into the structure during additive manufacturing, thereby dispersing the metal oxide in the structure.
[0014] The present invention will be described in detail below.
[0015] <Chemical composition of alloy> First, the chemical composition of the low thermal expansion laminated alloy of the present invention (hereinafter, sometimes simply referred to as "laminated alloy") will be described. Hereinafter, "%" regarding the chemical composition means "mass %". In addition, in the numerical range of the chemical composition, the numerical range expressed by "to" means a range including the numerical values written before and after "to" as the lower and upper limits.
[0016] (C: 0~0.010%) C is an element that increases the thermal expansion coefficient of the alloy. In addition, when melting during additive manufacturing, C reacts with oxygen to generate CO gas, which rises to the surface and is difficult to be incorporated into the structure, so the oxygen content in the additive alloy is low, and as a result, the metal oxide described below cannot be obtained in the additive alloy. Therefore, the C content is preferably low, and is set to 0.010% or less. C is not an essential element, and the C content may be 0. The C content may be 0.008% or less, 0.006% or less, 0.005% or less, or 0.004% or less.
[0017] (Si: 0 to 0.050%) Si is an element that increases the thermal expansion coefficient. In addition, if the Si content is high, Si reacts with oxygen during melting during additive manufacturing to generate oxides, which rise to the surface and are difficult to be incorporated into the structure, so the oxygen content in the additive alloy is low, and as a result, the metal oxide described below cannot be obtained in the additive alloy. Therefore, the Si content is preferably low, and is set to 0.050% or less. Si is not an essential element, and the Si content may be 0. The Si content may be 0.040% or less, 0.030% or less, 0.020% or less, 0.010% or less, or 0.005% or less.
[0018] (Mn: 0~0.050%) Mn is an element that increases the thermal expansion coefficient. In addition, if the Mn content is high, Mn reacts with oxygen during melting during additive manufacturing to generate oxides, which rise to the surface and are difficult to be incorporated into the structure, resulting in a low oxygen content in the laminated alloy, and as a result, the metal oxide described below cannot be obtained in the laminated alloy. Therefore, the Mn content is preferably low, and is set to 0.050% or less. Mn is not an essential element, and the Mn content may be 0. The Mn content may be 0.040% or less, 0.030% or less, or 0.020% or less.
[0019] (Ni: 30.00~37.00%) Ni is an element that reduces the thermal expansion coefficient. The low thermal expansion laminated alloy of the present invention has an average thermal expansion coefficient of 1.0×10 -6 / °C or less. This thermal expansion coefficient is mainly obtained by setting the contents of Ni and Co in appropriate ranges. If the Ni content is too high or too low, the thermal expansion coefficient will not be sufficiently small. In order to sufficiently reduce the thermal expansion coefficient, the Ni content is set to 30.00 to 37.00%. The Ni content may be 31.00% or more, 31.50% or more, 32.00% or more, or 32.50% or more. The Ni content may be 36.00% or less, 35.50% or less, 35.00% or less, 34.50% or less, or 34.00% or less.
[0020] (Co: 0-6.00%) Co, in combination with Ni, contributes to a decrease in the thermal expansion coefficient. Co is not an essential element, and the Co content may be 0. To obtain a desired thermal expansion coefficient, the Co content is 0 to 6.00%. The Co content may be 1.00% or more, 2.00% or more, or 3.00% or more. The Co content may be 5.80% or less, 5.60% or less, 5.50% or less, 5.40% or less, or 5.20% or less.
[0021] (O: 300-1000 ppm) O is an essential element for forming metal oxides in the austenite structure of the laminated alloy and increasing the strength (0.2% yield strength) of the laminated alloy. To obtain this effect, the O content is set to 300 ppm or more. If the O content is too high, pores are formed and, conversely, the 0.2% yield strength decreases. Therefore, the O content is set to 1000 ppm or less. The O content may be 400 ppm or more, 500 ppm or more, or 600 ppm or more. The O content may be 900 ppm or less, 850 ppm or less, or 800 ppm or less.
[0022] The balance of the chemical composition is Fe and inevitable impurities. The inevitable impurities are not intentionally contained in the steel when the steel having the chemical composition specified in the present invention is industrially produced, but are inevitably mixed in from the raw materials, the production environment, etc., and do not adversely affect the thermal expansion coefficient and 0.2% proof stress of the low thermal expansion laminated alloy according to the present invention.
[0023] (area ratio of metal oxide) The structure of the low thermal expansion laminated alloy of the present invention is austenite, and metal oxides are present in the austenite at an area ratio of 0.50 to 2.00%. The metal oxides are mainly Fe oxides (FeO, Fe3O4), and may contain composite oxides of Si, Mn, Fe, and Al. The area ratio of the metal oxides may be 0.60% or more, 0.70% or more, 0.80% or more, or 0.90% or more. The area ratio of the metal oxides may be 1.80% or less, 1.70% or less, 1.60% or less, or 1.50% or less.
[0024] The area ratio of the metal oxide is measured by observing the dark field image of the oxide using a transmission electron microscope (TEM). Specifically, a sample taken from the low thermal expansion laminated alloy is cut and polished from both sides to a thickness of 60 μm with #1200 emery paper, and a sample of φ3 mm is punched out. Next, double-sided jet electrolytic polishing is performed until a hole is made in the center to obtain a sample for TEM observation. For example, double-sided jet electrolytic polishing can be performed using a TenuPol manufactured by Struers as an electrolytic polishing device, 100 ml perchloric acid-800 ml glacial acetic acid solution-100 ml methanol as an electrolytic polishing solution, and electrolytic polishing conditions of 30 V and 0.1 A.
[0025] As the TEM, JEM-2100F manufactured by JEOL Ltd. can be used, and NBD (Nano Beam Diffraction) is used as the electron diffraction method, with an acceleration voltage of 200 kV and a probe diameter of 10 nm. The observation area by TEM is 3 μm×3 μm, and observation is performed in any 10 fields of view, and the area ratio of the metal oxide is calculated as the average value. FIG. 1 is an example of a dark field image of a TEM in which metal oxides in a structure are observed, and the white parts are metal oxides. The metal oxides have an average particle size of about 8 nm and are mainly dispersed in subgrain boundaries. By dispersing the metal oxides at an appropriate area ratio, the 0.2% proof stress is improved by particle dispersion strengthening. The low thermal expansion alloy of the present invention has a 0.2% proof stress at 23° C. of 360 MPa or more, preferably 370 MPa or more, 380 MPa or more, 390 MPa or more, or 400 MPa or more.
[0026] (Thermal expansion coefficient) The low thermal expansion laminated alloy of the present invention has an average thermal expansion coefficient of 1.00×10 at 18 to 28°C. -6 / °C or less. This thermal expansion coefficient can be obtained mainly by setting the contents of Ni and Co in appropriate ranges. The average thermal expansion coefficient at 18 to 28°C is 0.80×10 -6 / ℃ or less, 0.60×10 -6 / ℃ or less, 0.40×10 -6 / ℃ or less, 0.20×10 -6 / ℃ or less, or 0.00×10 -6 / °C or less.
[0027] The thermal expansion coefficient is measured using a thermal expansion measuring device in the range of 0 to 130° C. at a temperature increase rate of 3° C. / min to determine the average thermal expansion coefficient in the range of 18 to 28° C. As the thermal expansion measuring device, a DIL402C manufactured by NETZSCH can be used.
[0028] <Method of manufacturing low thermal expansion laminated alloy> Next, an example of the method for producing the low thermal expansion laminated alloy of the present invention will be described.
[0029] The low thermal expansion laminated alloy of the present invention is (1) A low thermal expansion laminated alloy is adjusted to have a desired chemical composition, and alloy powder is produced by an atomization method; (2) The resulting powder is irradiated with an electron beam or laser beam, melted and solidified, and layered to form the desired shape. The present invention can be produced by a production method including the steps of:
[0030] (Cast Steel Melting) First, the raw materials adjusted so that the low thermal expansion laminated alloy has a desired chemical composition are melted, and an alloy powder is obtained by gas atomization using Ar or N2. The obtained powder may be classified into a particle size of 5 to 200 μm for use. Classification may be performed using a sieve, or may be performed using other methods such as air flow classification. When using a powder bed fusion method as the additive manufacturing method described below, the particle size of the powder is preferably 45 μm or less in consideration of the flowability of the powder. When using a directed energy deposition method as the additive manufacturing method, if the particle size of the powder is too small, the powder feeding becomes poor, so the particle size of the powder is preferably 45 μm or more.
[0031] Alternatively, cast steel adjusted so that the low thermal expansion laminated alloy has a desired chemical composition may be melted, the resulting cast steel may be remelted in a melting furnace such as a high-frequency or induction furnace, and the alloy powder may be obtained by gas atomization using Ar or N2. In other words, the above-mentioned step (1) may be divided into two steps.
[0032] The gas pressure, gas flow rate, gas temperature, and convergence angle of the gas atomization method may be adjusted as appropriate. When a directed energy deposition method is used as the layered manufacturing method described later, the alloy powder may be obtained by a water atomization method instead of the gas atomization method. Since the circularity of the alloy powder obtained by the water atomization method is poor, when a powder bed fusion method in which the powder is spread on a bed is used as the layered manufacturing method, the fluidity is poor and it becomes difficult to fill, which makes it easy for defects to occur, and is not suitable. On the other hand, according to the directed energy deposition method, the powder is sprayed from a nozzle, melted by an electron beam or a laser beam, and layered, so that the alloy powder obtained by the water atomization method may be used.
[0033] (Additive Manufacturing) The obtained alloy powder is then irradiated with an electron beam or a laser beam to melt and solidify, thereby performing layer-by-layer manufacturing.
[0034] As the additive manufacturing method, Powder Bed Fusion (PBF) or Directed Energy Deposition (DED) can be used.
[0035] The conditions for additive manufacturing are, for example, energy density: 50 to 100 J / mm 3 It may be.
[0036] By carrying out additive manufacturing as described above, the low thermal expansion laminated alloy of the present invention can be obtained. The structure of the low thermal expansion laminated alloy of the present invention has a cell structure formed by sub-grain boundaries, and preferably the cell size is about 0.2 to 3.0 μm. The cell size may be 0.3 μm or more, 0.4 μm or more, 0.5 μm or more, 0.6 μm or more, or 0.7 μm or more. The cell size may be 2.8 μm or less, 2.5 μm or less, 2.0 μm or less, 1.8 μm or less, or 1.5 μm or less.
[0037] Although the embodiments of the present invention have been described above, the present disclosure is not limited to the above-mentioned embodiments, and various design changes can be made within the scope of the spirit of the present disclosure. According to the present invention, a low thermal expansion laminated alloy having high 0.2% yield strength can be obtained, which is suitable for, for example, a mold material for CFRP having a complex shape, a main shaft material (spindle), etc. EXAMPLES
[0038] <Example 1> The raw materials were adjusted so that the chemical composition of the low thermal expansion laminated alloy was the composition No. 1 in Table 1, and melted in a melting furnace, and alloy powder was produced by gas atomization using N2. The obtained powder was irradiated with a laser beam by the PBF method, melted and solidified, and additive manufacturing was performed to obtain the laminated alloy. The additive manufacturing conditions were energy density: 70 J / mm 3 The laminated alloy was prepared into a rod having a size of 20 mm square and a length of 150 mm, and a number of such rods were prepared for the tests described below.
[0039] <Invention Examples 2 to 5, Comparative Examples 6 to 13> A laminated alloy was produced in the same manner as in Example 1, except that the chemical composition was as shown in Table 1, and the lamination method and atomization method were as shown in Table 1. Regarding the atomization method in Table 1, "gas" means that the alloy powder was produced by gas atomization using N2, and "water" means that the alloy powder was produced by water atomization.
[0040] <Comparative Example 14> Cast steel having the chemical composition shown in Table 1 was melted, and the resulting cast steel was heated to 1200°C in a heating furnace and then subjected to hot forging. A forging process was performed so that the forging ratio was 25, and a round bar (forged alloy) having a diameter of φ20 mm was obtained.
[0041] For the obtained laminated alloy and forged alloy, the area ratio of metal oxide, the thermal expansion coefficient, and the 0.2% yield strength were determined as follows.
[0042] (area ratio of metal oxide) A sample taken from the low thermal expansion laminated alloy was cut and polished on both sides to a thickness of 60 μm with #1200 emery paper, and a sample with a diameter of 3 mm was punched out. Next, double-sided jet electrolytic polishing was performed until a hole was made in the center to prepare a sample for TEM observation. The double-sided jet electrolytic polishing was performed using a TenuPol manufactured by Struers as the electrolytic polishing device, 100 ml perchloric acid - 800 ml glacial acetic acid solution - 100 ml methanol as the electrolytic polishing solution, and the electrolytic polishing conditions were 30 V, 0.1 A.
[0043] The TEM used was a JEM-2100F manufactured by JEOL Ltd., and the electron diffraction method was NBD (Nano Beam Diffraction), with an acceleration voltage of 200 kV and a probe diameter of 10 nm. The observation area by TEM was 3 μm × 3 μm, and observation was performed in 10 fields of view. The average value of the area ratio of the metal oxide in each field of view was taken as the area ratio of the metal oxide of the sample.
[0044] (Thermal expansion coefficient) The thermal expansion coefficient was measured using a thermal expansion measuring device in the range of 0 to 130°C at a temperature increase rate of 3°C / min, and the average thermal expansion coefficient in the range of 18 to 28°C was obtained. The thermal expansion measuring device used was a DIL402C manufactured by NETZSCH. In this example, the average thermal expansion coefficient in the range of 18 to 28°C was 1.0×10 -6 / °C or less was determined to be a low thermal expansion coefficient.
[0045] (0.2% yield strength) From the manufactured low thermal expansion laminated alloy, a No. 14A bar-shaped tensile test piece as specified in JIS Z 2241:2011 was taken so that the tensile direction was parallel to the lamination direction, and a tensile test was carried out according to JIS Z 2241:2011 to measure the 0.2% yield strength. The test temperature was 23°C. In this example, if the 0.2% yield strength was 360 MPa or more, it was determined that the 0.2% yield strength was high.
[0046] The results are shown in Table 1.
[0047] [Table 1]
[0048] Comparative Example 6 is a comparative example having a high C content. It is considered that the high C content prevented sufficient metal oxide from being formed in the structure. As a result, the 0.2% proof stress was low.
[0049] Comparative Example 7 is a comparative example with a high Si content. It is considered that the high Si content prevented sufficient metal oxide from being formed in the structure. As a result, the 0.2% proof stress was low.
[0050] Comparative Example 8 is a comparative example having a high Mn content. It is believed that the high Mn content prevented sufficient metal oxide from being formed in the structure. As a result, the 0.2% proof stress was low.
[0051] Comparative Example 9 is a comparative example in which the Ni content is low. As a result, the average thermal expansion coefficient at 18 to 28° C. was large.
[0052] Comparative Example 10 is a comparative example in which the Ni content is high. As a result, the average thermal expansion coefficient at 18 to 28° C. was large.
[0053] Comparative Example 11 is a comparative example having a large content of Co. As a result, the average thermal expansion coefficient at 18 to 28° C. was large.
[0054] Comparative Example 12 is a comparative example having a low content of O. It is considered that the low content of O prevented sufficient metal oxide from being formed in the structure, resulting in a low 0.2% proof stress.
[0055] Comparative Example 13 is a comparative example having a high content of O. It is considered that the high content of O caused too much metal oxide to be formed in the structure, resulting in the formation of pores. As a result, the 0.2% proof stress was low.
[0056] Comparative Example 14 is a comparative example of a forging alloy. Since a large amount of Si and Mn are added for casting, the amount of oxygen is low. Therefore, it is considered that metal oxides are not formed in the structure. As a result, the 0.2% proof stress is low.
[0057] On the other hand, in Examples 1 to 5 within the scope of the present invention, the area ratio of the metal oxide was 0.50 to 2.00%, and as a result, a low thermal expansion laminated alloy was obtained that had a small thermal expansion coefficient and a high 0.2% proof stress.
Claims
[Claim 1] In mass percent, C: 0 to 0.010%, Si: 0 to 0.050%, Mn: 0 to 0.050%, Ni: 30.00-37.00%, Co: 0-6.00%, O: 300-1000ppm The balance being Fe and unavoidable impurities; The area ratio of metal oxide in austenite is 0.50 to 2.00%; The average thermal expansion coefficient at 18 to 28°C is 1.00 x 10 -6 / ℃ or less A low thermal expansion laminated alloy.
Citation Information
Patent Citations
Low-thermal expansion alloy excellent in low-temperature stability, and manufacturing method thereof
JP2022035111A
Method for heat-treating laminated molding and method for producing low thermal expansion alloy molding
JP2022047833A